A Nobel Chemiluminescence and Fluorescence Energy Transfer Three Inlets Cell for the Determination of Hydrogen Peroxide via Continuous Flow Injection Analysis - Nagam Shakir Turkie Al-Awadi (Journal of Global Pharma Technology, 2016)
The study presents a sensitive, fast and easy assay method that was developed for determination of hydrogen peroxide  via continuous mode of FIA i.e. new noble chemiluminescence and fluorescence cell with specially designed unit cell of three inlets and  one outlet  to measure a total luminescence which include the chemiluminescence generated and the fluorescence that was created by the in situ radiation of the released chemiluminescence light using fluorescence molecule which gives an emission spectrum at 530 nm The method is based on the use of fluorescent molecule as an acceptor fluorophore where by it is irradiated internally and instantly when the generation of luminol chemiluminescence light is used as internal source for irradiation of fluorescein molecule to give fluorescence light , this reaction and analysis occur in a specially homemade  designed cell. Experimental parameters that lead to optimum concentrations of all chemicals and physicals variables .A sample volume of 75 μL was used throughout the whole work. It was found that the linear working range was between 20-500 μmol. L-1, with correlation coefficient of 0.9969 and limit of detection L.O.D. (S/N =3) 1.275ng/sample by using step wise dilution of the minimum concentration that was achieved by the calibration graph. Repeatability of less than 0.25% for ten successive injections of 250 μmol.L-1 & 400μmol .L-1 of hydrogen peroxide .The method was applied successively in determination of hydrogen peroxide in some pharmaceutical disinfectants.Keywords: Chemiluminescence, Flow injection analysis, Hydrogen peroxide, In situ fluorescence.